SISTEM INFORMASI AKUNTANSI PENDAPATAN PADA KOPERASI SEDANA MERTA JATI DI DESA DARMASABA - Kadek Ayu Kreistya Dewi (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2022)
Accounting information system is a series of procedures in collecting various data, processing the data into information and distributing it to interested parties. With the accounting information system, it is hoped that it can provide a network of procedures that are arranged in an integrated manner in carrying out smooth company activities. The cash income cycle describes the activities of a company in selling goods and services to customers starting from receiving orders, sending goods/services, billing, receiving payments to depositing cash and recording it. Sedana Merta Jati Cooperative is one of the business entities engaged in credit or savings and loans owned and managed by its members located in Banjar Bersih, Darmasaba Village, Abiansemal District, Badung. The Sedana Merta Jati Cooperative has used accounting information systems in its operational processes to achieve effective and efficient performance. The cash income of the Sedana Merta Jati Cooperative comes from cash receipts from receivables and deposits. Based on the results that have been observed, it can be concluded that the Cash Revenue Cycle from Receivables and Deposits is obtained by implementing the procedures for notification of receivables, billing procedures, procedures for cash receipts, and procedures for recording cash receipts. The income cycle accounting information system at the Sedana Merta Jati Cooperative has been carried out effectively in accordance with the assignment functions, namely administrative and general functions, collection functions (collectors/accompaniments), financial functions/cashier functions and computerization functions.